Analysis needs assessment to development students' digital intelligence. Savannakhet University, Lao PDR: https://doi.org/10.69692/SUJMRD0802187 - PHONESAY, Latsamy; GUMJADPAI, Sumran; KUNPAIBUTR, Thananun (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The purpose of this research was to 1) Study the elements of student digital intelligence. Savannakhet University 2) study the needs to developing students' digital intelligence. Savannakhet University. The sample of this research consisted of 352 students. The research instrument was the expectation questionnaire. And the reality of digital intelligence in using of digital technologies in the online. The confidence values ​​were 0.94 and 0.93, respectively. The statistics used in the data analysis were percentage, Mean, Standard Deviation. And the priority need index. The findings revealed as follows: 1) The digital intelligence was composed of 8 components: Digital Citizen Identity, Critical thinking, Cybersecurity Management, Privacy Management, Screen Time Management, Digital Footprints, Cyberbullying Management, and Digital Empathy. And from the results of the suitability assessment of the components by 18 experts, it was found that all components were at the highest level. And overall every element is at the highest level. 2) the expectation in development digital intelligence in the use of digital technologies in the online, in the overall 8 elements, was at the highest level. The current reality about digital Intelligence in using digital technology in the online in all 8 elements is moderate. And it was found that the priority need index (PNImodifies), in the overall of the 8 elements was 0.74, which was positive. Show that the current reality about digital Intelligence in using digital technology in the online there is less than expected by the rate of change in development from the actual situation to the expected condition is 0.74 or 74%, which is considered a high need for development.